Conveniently pessimistic: manipulating beliefs to excuse selfishness in charitable giving - Samad, Zeeshan (Frontiers in Behavioral Economics, 2024)
This paper demonstrates how people can manipulate their beliefs in order to obtain the self-image of an altruistic person. I present an online experiment in which subjects need to decide whether to behave altruistically or selfishly in an ambiguous environment. Due to the nature of ambiguity in this environment, those who are pessimistic have a legitimate reason to behave selfishly. Thus, subjects who are selfish but like to think of themselves as altruistic have an incentive to overstate their pessimism. In the experiment, I ask subjects how optimistic or pessimistic they feel about an ambiguous probability and then, through a separate task, I elicit their true beliefs about the same probability. I find that selfish subjects claim to be systematically more pessimistic than they truly are whereas altruistic subjects report their pessimism (or optimism) truthfully. Given the experiment design, the only plausible explanation for this discrepancy is that selfish subjects deliberately overstate their pessimism in order to maintain the self-image of an altruistic person. Altruistic subjects, whose behavior has already proven their altruism, have no such need for belief manipulation. JEL Classifications C91, D82, D83, D84.